2015
DOI: 10.1038/srep16331
|View full text |Cite
|
Sign up to set email alerts
|

Role of KRAS-LCS6 polymorphism in advanced NSCLC patients treated with erlotinib or docetaxel in second line treatment (TAILOR)

Abstract: MicroRNAs were described to target mRNA and regulate the transcription of genes involved in processes de-regulated in tumorigenesis, such as proliferation, differentiation and survival. In particular, the miRNA let-7 has been suggested to regulate the expression of the KRAS gene, a common mutated gene in non-small cell lung cancer (NSCLC), through a let-7 complementary site (LCS) in 3′UTR of KRAS mRNA. We have reported the analysis performed on the role of the polymorphism located in the KRAS-LCS (rs61764370) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…EGFR-TKI treatment for NSCLC have an impressive profile of therapeutic responses and ADR compared with standard chemotherapies. Previous studies showed relationships between both somatic activating mutations in EGFR coding sequences and SNP of drug metabolism genes with therapeutic responses to EGFR-TKI (Ganzinelli et al, 2015 ; Lópezayllón et al, 2015 ; Ruan et al, 2016 ). For example, rs884225 in EGFR is associated with erlotinib-induced ADR.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR-TKI treatment for NSCLC have an impressive profile of therapeutic responses and ADR compared with standard chemotherapies. Previous studies showed relationships between both somatic activating mutations in EGFR coding sequences and SNP of drug metabolism genes with therapeutic responses to EGFR-TKI (Ganzinelli et al, 2015 ; Lópezayllón et al, 2015 ; Ruan et al, 2016 ). For example, rs884225 in EGFR is associated with erlotinib-induced ADR.…”
Section: Discussionmentioning
confidence: 99%
“…The rs11615, rs3212986, rs17655, and rs1047768 SNPs were genotyped using MGB probes specifically designed for Allelic Discrimination and TaqMan SNP Genotyping assay (Applied Biosystems, Monza, Milan), based on real-time PCR technique (ABI 7900, Applied Biosystems). Polymerase chain reaction was performed in 384-well plates, as previously described in detail (34, 35). Allelic Discrimination Sequence Detection Software (Applied Biosystems) was used for the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In the last decade, many studies have been published analyzing the prognostic and predictive roles of KRAS SNPs rs10771184 and rs61764370 in miRNA binding sites of the KRAS gene. And while several studies emphasized the potential role of these SNPs as molecular biomarkers in various tumors for disease susceptibility [56,57], prognosis [18,58], survival [59,60], and prediction of drug response [61], others found no correlation [62,63]. However, to the best of our knowledge, we are the first study to publish an association between these two polymorphisms and KRAS protein expression.…”
Section: Discussionmentioning
confidence: 78%